Pemberdayaan Kader Posyandu Dalam Meningkatkan Kesehatan Lansia Melalui Senam Lansia - Edy Prawoto; Raudhotun Nisak; Tri Admadi (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2021)
Background: Aging is one cycle of life that will be   experienced by everyone. There are many changes occur, especially physical conditions such as reduced muscle mass, myofibril degeneration, tendon contraction, and atrophy of muscle fibers and one of solution was elderly exercise. Purpose: The role of health cadres in improving the health of the elderly is very important in the activities of the elderly posyandu. Method: This community service method is carried out with an analytical survey which is then carried out in 3 forms of activity including counseling about elderly gymnastics to cadres and the elderly, elderly gymnastics training to elderly posyandu cadres, and elderly gymnastics activities. Results: The results of this activity showed an increase in knowledge, gymnastic skills in elderly cadres and increased participation of the elderly in participating in gymnastics. Conclusion: Cadres have an important role in improving the health status of the community, especially the elderly, so they must be equipped with knowledge and skills, one of which is elderly gymnastics.